Subak Berbasis Tri Hita Karana Dalam Melestarikan Dan Mempertahankan Pariwisata Budaya Di Era Modern Di Kabupaten Gianyar - I Wayan Eka Artajaya (Universitas Mahendradatta, 2019)
Bali as a place of tourism it has its own attraction than with the other touris, the appeal ofthe island of Bali which is in the field of tourism from the beauty of nature, the beauty of thebeaches, diverse arts and culture. One of the uniqueness that can attract tourists to come tothe island of bali is tourism in the field of terasering the ones in familiar wits this traditionalsubak. Along with the development of a more modern, irrigation system traditionally, hasbeen on leave by Sekaha tiller and switched to using the increasingly sophisticated. Subakbased on Tri Hita Karana in preserving and maintaining of tourism cultur in the era ofmodern in Gianyar. Discussion Tri Hita Karana with his village Pakraman is the last fortress to preserve the security and protecting the culture of bali, especially on iririgation systemsubak in Gianyar that has become a world heritage. The subak be done with theestablishment of a awig-awig the ban on the use of machines and chemicals in an irrigationsystem subak and awig-awig associated over the functions of agricultural land, so that theachievement of the subak based on Tri Hita Karana.